2013
DOI: 10.1021/ja310186g
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organization of Lipid Phases in Micropatterned Polymer-Supported Membranes

Abstract: We have established an approach for the spatial control of lipid phase separation in tethered polymer-supported membranes (PSMs), which were obtained by vesicle fusion on a poly(ethylene glycol) polymer brush functionalized with fatty acid moieties. Phase separation of ternary lipid mixtures (1,2-dioleoyl-sn-glycero-3-phosphocholine/sphingomyelin/cholesterol) into liquid-disordered (l(d)) and liquid-ordered (l(o)) phases within both leaflets was obtained with palmitic acid as the anchoring group. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Monomeric EGFP was obtained by the A206K mutation within the EGFP sequence of pEGFP-N1 (Clontech). An artificial transmembrane domain (TMD) with the sequence AS ALAALAALAALAALAALAALA KSSRL (ALA7) (as described by 64 ) extracellular fused to HaloTag (Promega) and mTagBFP (obtained from Vladislav Verkhusha, New York 65 ) and intracellularly fused to human STAT2 was cloned into pDisplay ™ (Invitrogen). For cloning of pSEMS-HaloTag®-IFNAR2, the gene coding for the HaloTag followed by the genes of full length IFNAR2 or IFNAR2Δ375 without the N-terminal signal sequences were inserted into pDisplay (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Monomeric EGFP was obtained by the A206K mutation within the EGFP sequence of pEGFP-N1 (Clontech). An artificial transmembrane domain (TMD) with the sequence AS ALAALAALAALAALAALAALA KSSRL (ALA7) (as described by 64 ) extracellular fused to HaloTag (Promega) and mTagBFP (obtained from Vladislav Verkhusha, New York 65 ) and intracellularly fused to human STAT2 was cloned into pDisplay ™ (Invitrogen). For cloning of pSEMS-HaloTag®-IFNAR2, the gene coding for the HaloTag followed by the genes of full length IFNAR2 or IFNAR2Δ375 without the N-terminal signal sequences were inserted into pDisplay (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…By using a patterning of polymers with either a saturated or an unsaturated lipid, the binding of particular lipids to the surface was altered leading to the recruitment of certain membrane components. 27,28 Alternatively, Morigaki and coworkers [29][30][31] used polymers that were partially or fully removed in confined areas to control membrane adhesion to the surface. They found that the l o -phase is localized in areas without polymer coating and the l d -phase in areas with partial polymer coating.…”
Section: Introductionmentioning
confidence: 99%
“…The L o /L d partitioning of urokinase receptors and integrin has been evaluated in SPBs (19,20). Micropatterning techniques can also be applied to SPBs for generating a patterned array of L o and L d domains (21,22). SPBs with spatially well-defined membrane domains should provide a robust and scalable platform for systematically and quantitatively studying the raftophilicity of a wide variety of membrane proteins.…”
Section: Introductionmentioning
confidence: 99%